Comparative Analysis of Green Smart Cities Policies in Russia and China Based on SWOT Analysis - Ying Liu; S. A. Stepanov (Евразийская интеграция: экономика, право, политика, 2025)
With the in-depth development of Big Data and artificial intelligence, as well as the strengthening of the concept of green and low-carbon development, a new concept has emerged in the system of urban functioning — “green smart city”. Currently, the level of urbanization and urban development in Russia and China is growing from year to year, but at the same time, issues of socio-ecological development, rational use of resources and innovative development are becoming increasingly relevant. In this regard, it is necessary to intensify efforts to optimize urban systems, promote rational allocation of resources and promote the construction of green smart cities. Aim. Assessment and forecasting of the level of development of green smart cities, which contributes to the formation of scientifically sound strategies for government agencies, and also plays an important role in promoting rational allocation of resources and the creation of a comfortable and favorable urban environment. Methods. In the process of work, historical and institutional methods were used (when analyzing the history of the development of smart cities), as well as conceptual content analysis (when studying the main documents on the construction of a green smart city from Russian and Chinese government agencies, international organizations, consulting firms and etc.), as well as statistical analysis of secondary data. This paper conducts a comparative analysis of the current status of environmentally sustainable smart cities in China and Russia from the perspective of four aspects: strengths, weaknesses, opportunities and threats. Results. The hypothesis of the paper is that Russia’s smart green city policy is a combination of centralized leadership and local pilot projects, with more attention paid to cybersecurity and infrastructure improvement, as well as promoting the integration of the green economy. China’s smart green city policy is systemic and executive in nature, and pays more attention to the application of artificial intelligence and 5G in the construction of smart green cities, promoting the development of green and low-carbon cities. Conclusions. The conclusion of the paper is that the approaches of Russia and China can be integrated. In the future, China can help Russia accelerate the development of 5G, Artificial Intelligence (AI) and the Internet of Things (IoT), which will improve the infrastructure of green smart cities in Russia. In turn, Russia can provide China with technological support in the field of smart security and energy management, which will enhance the level of green smart cities in China.